Design and development of facial recognitionbased library management system (FRLMS) - Rao, Vegnish Rao Paramesura; Puwakpitiyage, Chamode Anjana Hewawasam; Abdulkareem Shafiq, Dalia; Islam, Farhana; Handayani, Dini Oktarina Dwi; Yaacob, Hamwira Sakti; Mantoro, Teddy (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper we propose a facial recognitionbased library management system namely Facial Recognition based Library Management System (FRLMS). This system aims to improve the user experience on library authentication process through facial recognition algorithm. This process would be simple and efficient as the authentication process is performed seamlessly. For the purpose of this study, feature extraction and image classification are obtained using OpenCV and TensorFlow, where the average recognition accuracy reaches up to 92.15%